2022
DOI: 10.1371/journal.pone.0261965
|View full text |Cite
|
Sign up to set email alerts
|

Development and Validation of Clinical Diagnostic Model for Girls with Central Precocious Puberty: Machine-learning Approaches

Abstract: Background A brief gonadotropin-releasing hormone analogues (GnRHa) stimulation test which solely focused on LH 30-minute post-stimulation was considered to identify girls with central precocious puberty (CPP). However, it was tested using traditional statistical methods. With advanced computer science, we aimed to develop a machine learning-based diagnostic model that processed baseline CPP-related variables and a brief GnRHa stimulation test for CPP diagnosis. Methods We recruited girls suspected of precoc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 40 publications
1
13
0
Order By: Relevance
“…To date, there is an increasing emphasis on basal sex hormone levels for diagnosing CPP because of the insurmountable drawbacks of the nonphysiological GnRH stimulation test, which does not truly re ect the level of gonadal development and requires multiple blood samples. Huynh [7] simpli ed the procedure of the GnRH stimulation test, reducing the duration and number of blood collections, however, it still used the method of stimulation test. Given that the GnRH stimulation test is cumbersome to perform and that overdiagnosis of CPP due to false positives after the GnRH stimulation test has been documented in the infant population[8], the possibility of replacing this test with a simpli ed evaluation panel including basal laboratory hormonal values, such as LH, and pelvic ultrasonography, which is noninvasive and relatively easy to perform, has been continuously reviewed over the years [9][10][11][12][13][14][15][16][17][18][19][20][21][22][23].…”
Section: Discussionmentioning
confidence: 99%
“…To date, there is an increasing emphasis on basal sex hormone levels for diagnosing CPP because of the insurmountable drawbacks of the nonphysiological GnRH stimulation test, which does not truly re ect the level of gonadal development and requires multiple blood samples. Huynh [7] simpli ed the procedure of the GnRH stimulation test, reducing the duration and number of blood collections, however, it still used the method of stimulation test. Given that the GnRH stimulation test is cumbersome to perform and that overdiagnosis of CPP due to false positives after the GnRH stimulation test has been documented in the infant population[8], the possibility of replacing this test with a simpli ed evaluation panel including basal laboratory hormonal values, such as LH, and pelvic ultrasonography, which is noninvasive and relatively easy to perform, has been continuously reviewed over the years [9][10][11][12][13][14][15][16][17][18][19][20][21][22][23].…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have investigated whether only basic clinical information and various baseline sex hormones can be used to discriminate between ICPP and PPP, but none have been able to propose a reliable model that can be used for diagnosis. 18,20,21 An exploratory study has investigated the use of pelvic ultrasound to identify PP and premature thelarche (PT) and found that increased uterine and ovarian measurements may be an early and sensitive sign of PP. 21 One study developed a clinical risk model by ultrasound to assess the risk of CPP in girls with a model consistency index (C-index) of 0.85 in the training group.…”
Section: Discussionmentioning
confidence: 99%
“…It has been suggested that baseline LH is sufficient as a negative diagnostic power for ICPP, but a stable positive diagnostic power is lacking 31 . Moreover, a recent study used a random forest algorithm to build a classification model which included baseline clinical data, baseline sex hormones, and LH values at 30 minutes of a GnRH stimulation test which resulted in an excellent AUC (0.972) 18 . However, that study still adopted the reference standard GnRH stimulation test, and while the results were better than those in our study, patients still required multiple blood sampling, which was inconsistent with the goals of our study.…”
Section: Discussionmentioning
confidence: 99%
“…This can either lead to arrested and delayed growth or accelerated fusion of the physis and premature skeletal development, thereby depicting precocious puberty and referring patients to specialists early on in their disease. [48][49][50] Reduced variability, bone age accuracy, and rootmean-squared error improves after implementing AI-enabled diagnosis of radiologists when compared with AI alone, a radiologist alone, or a pooled cohort of experts. 50,51 AI applications demonstrate a promising role in detecting and monitoring metabolic bone diseases.…”
Section: Advantages and Future Of Artificial Intelligence On Imaging ...mentioning
confidence: 99%